(3hUjI GdEeGe CHj MfjaI GdfYeGf dJdejPg jhSa Hf NGdO GdSeJj GdHUQjs - (3GdJjej, Gdchaj, CHh MfjaI, GdfYeGf Hf KGHJ, J (B150 (3g`s
(3ChdgG (B:s
(3gPg hUjI GdEeGe CHj MfjaI dJdejPg jhSa Hf NGdO GdSeJj GdHUQj hUi HgG Mjf GSJCPfg Edi hWfg GdHUQI abGd(B: (3dG MJi CJbOe Ydjcs
(3BNQgG (B:s
(3aEfc Ef JeScJ HhUjJj gPg QLhJ Cf JSde hJYjT SGdeG Ef TGA Gddg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 36s
(3eYLe GdeDdajf(B: 4 / 32s
(3cTa GdXfhf(B: 2 / 2015s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs